PANCREATIC FRACTURE: CASE REPORT OF A RARE INJURY - Sridharan, R; Abdullah, BJJ (The ASEAN Journal of Radiology, 2023)
Blunt injuries of the pancreas are difficult to diagnose and require a high index of suspicion for diagnosis. A prolonged interval between injury and diagnosis is a recognized problem. It is important to detect blunt pancreatic injuries early as the mortality can be high (20%).’ There is also a high incidence of major complications such as pseudocysts, abscesses, haemorrhages or pancreatic fistulae in the survivors. We highlight the radiological features of a case of pancreatic fracture following blunt abdominal trauma and discuss the problems in diagnosis.